Influencer Economy and Consumer Behavior: A Conceptual Analysis of Digital Marketing’s Economic Effects - Filiz Kutluay Tutar; Abdallah Abukalloub; Ayşe Güngör (CV. Media Digital Publikasi Indonesia, 2026)
This study examines the influencer economy as a foundational component of the digital economy, exploring how digital marketing drives consumer behavior within platform-based markets. Utilizing a conceptual and literature-based approach, the research synthesizes recent studies across digital marketing, consumer behavior, platform economics, and digital labor. To move beyond fragmented perspectives, this study introduces the Value-Conversion Model of Influencer Markets. The analysis demonstrates that digital influence operates through a sequential progression: macro-level structural conditions (algorithmic governance, platform infrastructure, and digital labor) dictate market access; relational mechanisms (source credibility, perceived authenticity, and parasocial interaction) mediate audience persuasion; and behavioral constructs capture the final micro-level economic value (purchase intention, symbolic consumption, and brand loyalty). By explicitly linking psychological mechanisms with the political economy of platforms, the paper situates influencer marketing within broader discussions of asymmetrical value extraction and platform capitalism. Finally, the study highlights significant research gaps related to datafication, regulatory transparency, and cross-platform differences, offering a comprehensive theoretical blueprint for future empirical research and policy development.